AntiSMASH 6.0: improving cluster detection and comparison capabilities. Issue Volume 49:Issue W1(2021) (12th May 2021) - Blin, Kai; Shaw, Simon; Kloosterman, Alexander M; Charlop-Powers, Zach; van Wezel, Gilles P; Medema, Marnix H; Weber, Tilmann
Abstract: Many microorganisms produce natural products that form the basis of antimicrobials, antivirals, and other drugs. Genome mining is routinely used to complement screening-based workflows to discover novel natural products. Since 2011, the "antibiotics and secondary metabolite analysis shell—antiSMASH" (https://antismash.secondarymetabolites.org/ ) has supported researchers in their microbial genome mining tasks, both as a free-to-use web server and as a standalone tool under an OSI-approved open-source license. It is currently the most widely used tool for detecting and characterising biosynthetic gene clusters (BGCs) in bacteria and fungi. Here, we present the updated version 6 of antiSMASH. antiSMASH 6 increases the number of supported cluster types from 58 to 71, displays the modular structure of multi-modular BGCs, adds a new BGC comparison algorithm, allows for the integration of results from other prediction tools, and more effectively detects tailoring enzymes in RiPP clusters. Graphical Abstract: